2016
DOI: 10.1093/fampra/cmw101
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and management of perinatal depression and anxiety by general practitioners: a systematic review

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
44
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 45 publications
(82 reference statements)
3
44
1
1
Order By: Relevance
“…However, only 31% of respondents in a survey reported being asked by a GP about their mental well-being and whether or not they required any additional support (Royal College of Obstetricians and Gynaecologists, 2017). As a consequence, there appears to be substantial underrecognition of postnatal depression and other perinatal disorders in general practice (Gavin et al, 2015;Ford et al, 2016), and it is estimated that 50% of cases of postnatal depression currently go undiagnosed (Hewitt and Gilbody, 2009). This is likely to be due to two factors.…”
Section: Introductionmentioning
confidence: 99%
“…However, only 31% of respondents in a survey reported being asked by a GP about their mental well-being and whether or not they required any additional support (Royal College of Obstetricians and Gynaecologists, 2017). As a consequence, there appears to be substantial underrecognition of postnatal depression and other perinatal disorders in general practice (Gavin et al, 2015;Ford et al, 2016), and it is estimated that 50% of cases of postnatal depression currently go undiagnosed (Hewitt and Gilbody, 2009). This is likely to be due to two factors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the need to synthesise healthcare professionals (HCPs) experiences of providing care to women with PMHPs and to triangulate findings with the synthesis of women’s experiences has been identified [ 14 ]. A systematic review [ 15 ] examined quantitative studies on FPs recognition and management of perinatal depression and anxiety. Similarly, a meta-synthesis explored the diagnosis and management of perinatal depression and anxiety in general practice [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our recent systematic review of quantitative literature found large gaps in the literature and no studies on disorders other than depression (11). Qualitative research can provide a more detailed understanding of the complex factors that influence patient-clinician interactions and decisionmaking.…”
Section: Introductionmentioning
confidence: 99%
“…Following a review of quantitative observational studies in the same area (11), the aim of this review was to synthesise qualitative studies on GPs' attitudes, decision making and routine clinical practice for the diagnosis and treatment of perinatal depression and anxiety in primary care.…”
Section: Introductionmentioning
confidence: 99%